Enkätundersökning hos markägare inom SCA Skog Jämtlands förvaltning - Göransson, Fredrik (2013)
This report is a joint venture with SCA Skog AB in the Jämtland forest management area. The company is a major player in the timber market in northern Sweden, and also a large business globally with offices in over 100 countries. The purpose of the study was to find out how timber suppliers want feedback/follow-up after completion of timber business. To determine this, a questionnaire survey was sent out to 75 landowners who supplied the wood for the company during the past year. The questionnaire consisted of a total of 15 questions with the opportunity to comment on certain issues. The response rate totaled 44 percent. The survey results show that customers want their feedback/follow-up a few weeks after completion of timber business. They prefer to be contacted by the timber purchaser either by phone or a personal meeting.